ANALISIS SIFAT FISIKOKIMIA DAN ORGANOLEPTIK TEPUNG GADUNG (Dioscorea hispida Dennst.) TERMODIFIKASI OLEH BAKTERI ASAM LAKTAT (BAL) ASAL ISOLAT WIKAU MAOMBO - Nafilawati, Waode (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2016)
The purpose of this stusy was to investigate the effect of application of lactic acid bacteria (LAB) to organoleptic of gadung flour consist of taste, colour, aroma, and texture. This research based on completely randomized design (CRD) with four treatment that variation of fermentation time consist of treatment without fermentation (F0), fermentation in 1 day (F1), fermentation in 2 days (F2) and fermentation in 3 days (F3). The result of organoleptic showed that gadung flour with fermentation treatment for 3 days (F3), there was significant effect to organoleptic assessment of taste 3,653% (preferred), colour 3,638% (preferred), aroma 3,531% (preferred) and texture 3,683% (preferred).